An open label, non-comparative pilot study to assess the efficacy and safety of a food supplement containing manna in pediatric functional constipation - Gafencu, Mihai; Barattini, Dionisio Franco; Rosu, Serban; Clemente, Andrea Martina; Ardelean, Marius; Murina, Filippo (Progress in Nutrition, 2018)
Objective. The primary objective of this study was to evaluate the efficacy and safety of the food supplement Physiomanna Baby® in pediatric patients with a history of functional constipation defined by Rome III criteria; secondary objective was to evaluate the adherence to the tested product in the enrolled children. Methods. The trial was designed as an open label, non-comparative pilot trial. In 3 Romanian sites (one community hospital and two private medical practice offices) 49 children (20 males, 29 females) aged 0 - 8 years were enrolled. The study was conducted between February 2016 and April 2016. The investigational product was administered as 1 g/kg in single daily oral administration from the first day and continued for a maximum of 3 days in the first week. If the constipation symptoms persisted, the children were treated in an additional cycle of treatment for a maximum of 3 days. Results. The number of Spontaneous Bowel Movements (SBM) per week has increased to normal after Physiomanna Baby® administration (from 1.80 ± 0.41 at baseline to 6.04±1.54 at day 8) evidencing a statistically significant difference (P-value